Evaluating the role of dry ports in the port-hinterland settings: Conceptual framework and the case of Vietnam - Lam Canh Nguyen (Elsevier, 2021)
Analyzing the dry ports’ impacts on different stakeholders is imperative for assessing the feasibility of a dry port project and promoting the collaboration among such parties to optimize the supply chain between inland customers and seaports. This paper aims at developing a conceptual framework to evaluate the role of dry ports from multi-criteria and multi-stakeholder approaches. Based on an extensive literature review, a hierarchy of evaluation criteria was developed from the perspectives of three main stakeholder groups, i.e. dry port users, seaport-based players and community. Interviews were then carried out to verify the face validity of the initially proposed framework given the context of Vietnam, followed by a survey assessing the dry port’s contributions. The findings highlight the major role of dry port users in driving the success of a dry port, while also recognizes significant roles of seaport-based players and the community. The study provides insights into how different stakeholder groups might value the contribution of dry ports and demonstrates that dry port characteristics have apparent impacts on their role as perceived by each group. Finally, this research points out the current issues of the Vietnamese dry port system and provides recommendations and managerial implications accordingly.